Supervision in Rural Schools - D. Rodney Chemberlain; Lee Goldsberry (Journal of Research in Rural Education, 1983)
This is a report of teachers' responses to the Survey of Supervisory Practices (SSP) in four rural, central Pennsylvania school districts. Six factors, which are statistically significant (.05 level), are related to teachers' perceptions of the helpfulness or supervision in the improvement of their classroom instruction.